2014
DOI: 10.1016/j.neuron.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Encoding of Perception, Memory, and Movement in a C. elegans Chemotaxis Circuit

Abstract: Brain circuits endow behavioral flexibility. Here, we study circuits encoding flexible chemotaxis in C. elegans, where the animal navigates up or down NaCl gradients (positive or negative chemotaxis) to reach the salt concentration of previous growth (the setpoint). The ASER sensory neuron mediates positive and negative chemotaxis by regulating the frequency and direction of reorientation movements in response to salt gradients. Both salt gradients and setpoint memory are encoded in ASER temporal activity patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
143
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 53 publications
21
143
1
1
Order By: Relevance
“…Revealing these features of the C. elegans nervous system at the sensory level itself suggests that signal processing and integration may be already implemented at the sensory level itself or at the interface between the sensory and the interneuron level. Indeed, sensory neurons have been shown to be specialized to compute and temporally differentiate chemosensory cues (25,26). Moreover, the structure of the neural network is shallow: We analyzed the C. elegans neural network and found that the average shortest path from each of the chemosensory neurons (at the sensory periphery) to the motor neurons (the most downstream elements in the nervous system) is 3.5 ± 0.8 synapses.…”
Section: Significancementioning
confidence: 99%
“…Revealing these features of the C. elegans nervous system at the sensory level itself suggests that signal processing and integration may be already implemented at the sensory level itself or at the interface between the sensory and the interneuron level. Indeed, sensory neurons have been shown to be specialized to compute and temporally differentiate chemosensory cues (25,26). Moreover, the structure of the neural network is shallow: We analyzed the C. elegans neural network and found that the average shortest path from each of the chemosensory neurons (at the sensory periphery) to the motor neurons (the most downstream elements in the nervous system) is 3.5 ± 0.8 synapses.…”
Section: Significancementioning
confidence: 99%
“…Optogenetic activation of the ASER neuron induced a transient increase in turning for animals on salt concentrations below the one they were raised at, but a decrease when the animal navigates above the one they were raised at. Thus, the ASER neuron mediates salt avoidance and attraction by regulating the frequency of reorientation movements in response to the gradient [61,65].…”
Section: Sensory Systemsmentioning
confidence: 99%
“…The dynamics of these organisms' decision-making are intimately linked to the properties of the underlying chemical or neural substrates (Segall et al, 1986; Korobkova et al, 2004; Miller et al, 2005; Chronis et al, 2007; Clark et al, 2007; Emonet and Cluzel, 2008; Suzuki et al, 2008; Asahina et al, 2009; Shimizu et al, 2010; Bretscher et al, 2011; Busch et al, 2012; Kato et al, 2014; Luo et al, 2014). In their natural environments, animals are confronted with variable and frequently conflicting inputs arriving via multiple sensory pathways.…”
Section: Introductionmentioning
confidence: 99%